Non $C^0$ Nonconforming Elements for Elliptic Fourth Order Singular Perturbation Problem (Journal of Computational Mathematics, 2005)
In this paper we give a convergence theorem for non $C^0$ nonconforming finite element to solve the elliptic fourth order singular perturbation problem. Two such kinds of elements, a nine parameter triangular element and a twelve parameter rectangular element both with double set parameters, are presented. The convergence and numerical results of the two elements are given.